A randomized crossover study to compare efavirenz and etravirine treatment - Nguyen, Alain; Calmy, Alexandra; Delhumeau, Cécile; Mercier, Isabelle K; Cavassini, Matthias; Fayet-Mello, Aurélie; Elzi, Luigia; Genné, Daniel; Rauch, Andri; Bernasconi, Enos; Hirschel, Bernard (AIDS (London), 2011)
Efavirenz (EFV) causes neuropsychiatric side-effects and an unfavourable blood lipid profile. We investigated the effect of replacing EFV with etravirine (ETR) on patient preference, sleep, anxiety and lipid levels. Study participants did not complain of side-effects, had tolerated EFV for at least 3 months, with less than 50 copies/ml HIV-RNA. After randomization, the ETR-first group started with ETR (400 mg daily) [DOSAGE ERROR CORRECTED] with EFV-placebo and the EFV-first group with EFV with ETR-placebo. After 6 weeks, both groups switched to the alternate regimen. Nucleoside reverse transcriptase inhibitors were continued without any change. The primary end point was patient preference for the first or the second regimen, assessed after 12 weeks. Fifty-eight patients were enrolled with a median CD4 cell count of 589 cells/μl and the duration of previous EFV therapy was 3.9 years. Fifty-five patients completed the study. When asked about treatment preference after 12 weeks, 16 preferred EFV and 22 preferred ETR, whereas 17 did not express a preference (P = NS). Patients who continued EFV during the first phase of the trial preferred EFV (15/21, 71%), whereas patients who started with ETR were more likely to prefer ETR (n = 16/17, 94%). This order effect was strongly significant (P < 0.0001). Quality of sleep, depression, anxiety and stress scores did not differ significantly between groups. Median plasma cholesterol levels decreased by 0.7 mmol (29 mg/100 ml) after replacing EFV with ETR (P < 0.002). After substitution of EFV by ETR, patients did not express a significant preference for ETR. There was no measurable effect on neuropsychiatric symptoms and sleep. Cholesterol decreased.